Emerging investigators series: untangling the microbial ecosystem and kinetics in a nitrogen removing photosynthetic high density bioreactor. Issue 4 (26th April 2016) - Price, Jacob R.; Keshani Langroodi, Saeed; Lan, Yemin; Becker, Jonas M.; Shieh, Wen K.; Rosen, Gail L.; Sales, Christopher M.
Abstract : Metabolic kinetics, microscopy, metagenomic analysis, and real-time PCR are applied to characterize nitrogen species transformation and identify and quantify the organisms key to these transformational processes. Abstract : An increasing number of water resource recovery facilities are implementing biological processes for nutrient removal and recovery. One challenge with engineering these processes is the kinetic characterization of nutrient dynamics within microbial communities, where metabolite sharing and varying ecological niches and strategies can lead to complex interactions among organisms. We have applied a 3-dimensional (3-D) visualization method to reveal the effects of varying proportions and total loading of inorganic N species (NH4 + and NO3 − ) on assimilatory and dissimilatory processes by a mixed photosynthetic community within a continuous high density bioreactor (HDBR). This 3-D method enabled the identification of loading conditions that result in maximum specific total N removal rates, which were not easily apparent with 1-dimensional linear regression. Furthermore, microscopic and metagenomic analyses enabled the identification of Chlamydomonas reinhardtii and Parachlorella kessleri as the two dominant algal strains and a member of the Leptolyngbya genus as the dominant cyanobacteria present within the community. Ammonia- and nitrite-oxidizing bacteria (AOB and NOB respectively) were found to comprise a small but significant portion of the bacterial community. Relative and absolute abundance of total bacteria, AOB, NOB, denitrifying bacteria, C. reinhardtii and P. kessleri were obtained from metagenomic and real-time PCR (qPCR) analyses. Within this work, we present evidence that the operational conditions and parameters of a reactor has an effect on each of the investigated components of the microbial community and that those effects ultimately impact the resultant reactor kinetics.